Comparison between supplementation with roughage and concentrate on growing performance of young horses - Furtado, Carlos E.; Tosi, Hugo; Santos, Gilberto de F.; Toledo, Luiz Roberto A.; Leão, José Felipe de S. (Pesquisa Agropecuaria Brasileira, 2014)
Sixteen fillies aged 9.5 months were submitted during 112 days to the treatments: A - concentrate at the rate of 1% of body weight; B - Guinea grass (Panicum maximum Jacq.); C – Alfafa hay (Medicago sativa L.); and D - Rhodes hay (Chloris gayana Kunth.) offered ad libitum plus protein supplement. Considering the daily gain of body weight the best performance was obtained with the animals of treatment A, which presented gains as foreseen in the previsions of feedings in three experimental periods (0.84, 0.52 and 0.70 kg/day), while treatment B made possible satisfactory gain in two periods (0.50 and 0.48 kg/day) and treatment C in one period (0.59 kg/day). The highest gain in height at the withers/period was obtained with treatment A (1.85 cm), which was superior (P ≤ 0.05) to those having treatment C and D, nevertheless, not differing from treatment B. There were not any statistical differences among treatment B, C and D. The average hearth girth/period gain was 4.37 cm, there not being any significant differences (P ≥ 0.05) among the treatments. The intake of treatment C varied from 36.25 to 75.13 g/kg0.75, while, on the other hand, treatment D, even though it had a low nutritive value, presented an intake of 17.56 to 78.95 g/kg0.75.